Biologics and small molecules in patients with scalp psoriasis: a systematic review. - Alsenaid, Adel; Ezmerli, Mohammad; Srour, Jerome; Heppt, Markus; Illigens, Ben M.; Prinz, Joerg C. (Journal of Dermatological Treatment, 2022)
BACKGROUND: Scalp psoriasis is common in psoriasis patients, difficult to treat and manifests a significant burden on quality of life. OBJECTIVE: Efficacy assessment of biologics and small molecules in scalp psoriasis with reported safety and quality of life. METHODS: Biological therapies and small molecules licensed for treatment of plaque psoriasis are assessed. Fourteen studies reporting results from RCTs are included. Efficacy assessment is measured through improvement of Psoriasis Scalp Severity Index (PSSI), Scalp Physician Global Assessment (ScPGA) and/or Scalp-Specific Investigator's Global Assessment (ss-IGA). RESULTS: Among biologics measured by PSSI, brodalumab, secukinumab and in a subgroup ixekizumab showed high efficacy in moderate to severe scalp psoriasis. Both brodalumab and ixekizumab demonstrated rapid response within 2 weeks. Guselkumab was superior to adalimumab and ixekizumab was superior to etanercept. Apremilast showed long-term efficacy. Only few studies reported quality of life in treatment of scalp involvement which showed improvement. All treatments demonstrated acceptable safety profile. CONCLUSION: Effective treatment of scalp psoriasis is essential for improving the quality of life of psoriasis patients. Both Biologics and small molecules proved efficacy. This review may help choosing the appropriate treatment in cases where scalp psoriasis is the main complaint. A unified measurement tool for scalp psoriasis severity is needed to facilitate comparisons.
EVALuna2:415137